2021
DOI: 10.1080/20507828.2021.1888211
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning Platforms and the Confessional Subject

Abstract: Is there a connection between pedagogic practices of confessional reflectivity, online learning platforms, and the massively scaled surveillance of Higher Education student transactions via data analysis? It is the contention of this paper that there is an ideological and processual logic which connects these practices and platforms. It argues this logic has been benignly embedded in pedagogy, but has now become scaled via technologically deterministic paradigms, providing companies such as Pearson Ltd with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Therefore, the information collected and analyzed no longer stays within the physical boundaries of the institution, creating a privacy lax where third-party systems could manipulate the collected behavioral data to understand their preferences, drives, and aptitudes (Alier et al, 2021;Viberg et al, 2020;Williamson, 2016). Dare (2021) assumed that these massively scaled data on student-lecturer interactions were examples of the education sector falling prey to surveillance capitalism. Through participative observation, excessive literature review, and analysis of legal frameworks, particularly GDPR and FERPA, Alier et al (2021) concluded that technological advancements lead to a loss of control over personal information, making it challenging to ensure user confidentiality and privacy, the growth of data surveillance in the education sector.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the information collected and analyzed no longer stays within the physical boundaries of the institution, creating a privacy lax where third-party systems could manipulate the collected behavioral data to understand their preferences, drives, and aptitudes (Alier et al, 2021;Viberg et al, 2020;Williamson, 2016). Dare (2021) assumed that these massively scaled data on student-lecturer interactions were examples of the education sector falling prey to surveillance capitalism. Through participative observation, excessive literature review, and analysis of legal frameworks, particularly GDPR and FERPA, Alier et al (2021) concluded that technological advancements lead to a loss of control over personal information, making it challenging to ensure user confidentiality and privacy, the growth of data surveillance in the education sector.…”
Section: Introductionmentioning
confidence: 99%
“…According to Niculae [9], distance education may lead to miscommunication and misunderstanding between the instructor and the students. From another perspective, it is emphasized that there are some issues about the time and money required to be spent in order to use new technologies and programs, and in some cases there is a risk of causing inequality [6,11].…”
Section: Introductionmentioning
confidence: 99%